أول تسجيل لداء الأكريات Coccidiosis عند أسماك الكارب العادي Cyprinus carpio L. المستزرعة في مزرعة السن- سورية - حسن محمد; ديوب أمل; بركات زين (Latakia University Journal -Biological Sciences Series, 2014)
يهدف هذا البحث إلى التقصي عن الإصابة بداء الأكريات Coccidiosis عند أسماك الكارب العادي المستزرعة في مزرعة مصبّ السن (بانياس). شملت الدراسة 200 سمكة، جمعت عشوائياً خلال الفترة الممتدة من 6 / 6 / 2012 ولغاية 14 / 5 / 2013، بمعدل عينّة واحدة شهرياً عدا فصل الشتاء. وقد تمّ تشخيص داء الأكريات Coccidiosis في الجزء الأمامي لأمعاء الأسماك فقط وذلك لأول مرة في سورية في هذه الدراسة, وتبيّن أن المسبب له هو الطفيلي Goussia carpelli. بلغت نسبة الإصابة بالطفيلي Goussia carpelli (3 %)، وقد اقتصرت الإصابة على فصلي الربيع والصيف, إذ سجلت أعلى نسبة إصابة في فصل الصيف ( 5.4 %). وكانت نسبة الإصابة بداء الأكريات عند الذكور ( 17.6 %) أعلى مما هي عليه عند الإناث (1.6 %). كما سجلت أعلى نسبة إصابة عند الأسماك بعمر 16 شهراً, وبمتوسط طول 17.5 سم, ومتوسط وزن 95.84 غراماً. This study aimed at investigating the infection of cultured common carp ( Cyprinus carpio L. ) by coccidiosis in AL-Sinn fish farm. Two hundred individuals were randomly sampled during the period from 6/6/2012 to 14/5/2013 except winter. Diagnosis of Coccidiosis was made in anterior intestine of studed fish for the first time in Syria in this study. It caused by the parasite Goussia carpelli. The Goussia carpelli infection was found only in the spring and summer and the prevalence reached (3%), whereas the highest was recorded in the summer (5.4%). Our results showed that the males were more infected than females (17.6% and 1.6% respectively). The fish aged 16 months were the most infected (17.5 cm average length and 95.84g average weight).